Development of History Teaching Materials on the Subject of Indonesian Independence in the Inculcation of Nationalism Values for Grade XI Students of SMA Negeri 1 Kroya - Wardani, Ika Surya; Sunarjan, YYFR; Atno, Atno (Universitas Negeri Semarang, 2020)
The purpose of this study is to (1) Describe the development of teaching materials on the history of the independence of Indonesia in the cultivation of the values of nationalism grade XI. (2) knowing and analyzing the feasibility of handouts about essential events, Indonesia's 1945 proclamation of independence, as seen from the validation results, are performed by expert material and media experts as well as responses to teacher and student feedback. The methods used in this research are Research and Development with the qualitative approach with phases according to Borg & Gall, i.e., potential and problems, data collection, design validation, product design I, design revision I, design II, revision of Validation design II, and trial usage. Powerpoint and book packages are learning materials for use in the classroom. Conventional models, such as lectures, summarize teachers' use in teaching so that students ' reading interest is still low. Based on the results of the validation of the feasibility level of expert material and media expert handout showed results of 94.60% for stage I material validation and 96.01% for the validation of material phase II, as well as media validation to 97.44% for phase I and 98.57% for media validation phase II, besides getting the results of 93.42% teacher responses, as well as the results of the analysis of the responses of the students of 86.61% (both categories).